Vietnamese EFL students’ use of grammar learning strategies: patterns, performance, and pedagogical implications - Pham Duc Thuan; Pham Thi Tam (Institute of Advanced Engineering and Science, 2026)
There is a scarcity of research regarding the application of grammar learning strategies (GLS) in English-as-a-foreign-language (EFL) contexts. This study evaluates the use of GLS among 257 Vietnamese EFL students by analyzing their preferences, differences, and correlations with grammar performance. Data for the study were collected using the grammar learning strategy inventory (GLSI) and a grammar test. Descriptive statistics, independent samples tests, and Pearson correlation tests were utilized to examine strategy usage levels, gender and year-level differences, as well as correlations with grammar test scores. The results indicate a significant prevalence of GLS usage (overall mean of 3.5811) and social strategies were identified as the most frequently employed with a mean of 3.7245. No notable differences in strategy utilization were observed between genders or academic year levels, indicating a uniformity within the Vietnamese educational framework. Weak yet statistically significant correlations were observed between grammar test results with metacognitive strategies (r=0.179, p<0.01), affective strategies (r=0.123, p<0.05) and social strategies (r=0.114, p<0.05), suggesting that GLS contribute to grammar mastery, although they are not the sole determinants of success. Findings suggest integrating collaborative and metacognitive strategies into English grammar instruction to help foster more strategic and independent grammar learning habits among university learners.